IMPLEMENTASI POJOK BACA GUNA MENINGKATKAN MINAT BACA SISWA SDN 06 RANTAU ALAI - Khairunnisa Khairunnisa (Kampus Akademik Publiser, 2025)
This study is based on the fact that reading corners are effective in fostering students' reading habits and creating a learning environment that supports literacy. Recommendations are given to schools to continue developing reading corner facilities and involving the entire school community in literacy programs.